Mulches enhanced growth and yield of onion - Rachel, MG; Mondal, MMA; Pramanik, MHR; Awal, MA (Bangladesh Journal of Scientific and Industrial Research, 2018)
The experiment was conducted to investigate the effect of mulches on soil nutrients and microclimate status, growth and bulb yield of onion cv. Taherpuri. The experiment was comprised of six mulches viz., i) Control (no mulch), ii) Black polythene sheet, iii) White polythene sheet, iv) Rice straw, v) Water hyacinth and vi) Saw dust. Application of different mulches improved soil microclimates, increased plant growth and bulb yield over control. Among the mulches, black polythene mulch showed superiority in growth and yield contributing characters compared to other mulches, resulting the highest bulb yield. Bangladesh J. Sci. Ind. Res.53(4), 305-310, 2018